Особенности повреждаемости длительно эксплуатируемых сварных соединений паропроводов - Касьяненко, Игорь Викторович (Национальный технический университет "Харьковский политехнический институт", 2019)
Изучение особенностей использования теплоустойчивых сталей для паропроводов и элементов их систем применительно к их наработке в условиях ползучести свыше 270000 ч. позволило: установить причины повреждаемости сварных соединений; уточнить механизмы развития трещин ползучести и трещин усталости; установить связь структуры с повреждаемостью; выявить изменение структурного состояния. Обобщение особенностей повреждаемости позволило уточнить типовые схемы повреждаемости, что целесообразно для ее уменьшения. Выявили, что при наработке сварных соединений свыше 270000 ч. в условиях участившихся пусков-остановов их повреждаемость по механизму усталости заметно увеличивается. Представлены особенности использования теплоустойчивых сталей для паропроводов и их сварных соединений. Рассмотрены механизмы повреждаемости сварных соединений паропроводов, длительно эксплуатируемых в условиях ползучести. Представлена зависимость повреждаемости от концентрации напряжений и от состояния структуры сварных соединений. Уточнили известную схему повреждаемости сварных соединений паропроводов применительно к их наработке свыше 270000 ч.

The aim of the work is to identify the features of damageability of welded joints of heat-resistant steels (12Х1МФ, 15Х1М1Ф) for long-term creep exploitation. To achieve the goal in the study of the structure and damage, metallographic methods and methods for determining mechanical properties were used. Studying the peculiarities of using heat-resistant steels for steam pipelines and elements of their systems as applied to the production of power-generating blocks under creep conditions over 270.000 hours allowed: to establish the reasons for their damageability and destructibility; mechanisms for the development of creep cracks and fatigue cracks; connection structure with damage; structural changes. Established the relationship of damage with the presence of stress concentrators. The generalization of features of damage allowed to specify typical patterns of damage, which is advisable to reduce it. It was revealed that when welded joints are produced for more than 270.000 hours under the conditions of frequent start-stops of power units, their damage by the fatigue mechanism increases markedly. Revealed that damage by the mechanism of fatigue significantly depends on the structural state of the steam lines and their welded joints.
Specific features of the damageability of the welded joints of steam pipelines that have been in service for a long time
Keywords: теплоустойчивые стали; структурное состояние; условия ползучести; heat-resistant steels; structural state; creepage conditions